PENDAMPINGAN PENYUSUNAN LAPORAN ARUS KAS DAN LABA RUGI BERBASIS PENGELOLAAN BIAYA PRODUKSI BAGI UMKM SARAPAN PAGI LELA - Fitri Novi Windu; Herlina Herlina; Nyayu Fadilah Fabiany; Sheilla Anggia Pratiwi; Sri Rahmadani (Jurnal Pengabdian Bukit Pengharapan, 2026)
This community service activity aimed to enhance the capabilities of Ibu Lela’s breakfast MSME in preparing cash books, income statements, and cash flow statements based on production cost management. The methods employed included outreach sessions and direct mentoring. The results indicate that the mentoring improved understanding regarding daily cash recording, the categorization of raw material and supply costs, and the preparation of simple income and cash flow statements. However, a comprehensive assessment of the MSME's financial status remains impossible due to the absence of financial records.